AN EXPLORATORY STUDY EVALUATING EXPERIENCED STIGMA AMONG DOCTORS IN A DEDICATED COVID-19 HOSPITAL OF NORTH INDIA - GARG, JASMIN; SINGLA, ADITI; GARG, ROHIT (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: Doctors may experience stigma and discrimination from community, friends and even family due to their association with COVID-19 patients. The present study was planned to assess actual stigma experienced by doctors because of working in COVID-19 wards. Methods: A cross-sectional study was conducted in the Department of Psychiatry of a dedicated COVID-19 Hospital of North India. A Google Survey Form which measured Experienced Stigma was circulated through WhatsApp groups in October-November 2020 among all the doctors working in COVID-19 ward. Data collected was analyzed statistically. Results: Around 250 doctors participated in the study and 70% of them experienced stigma in one or more ways. Approximately, 60% doctors had stopped socializing because of people’s reactions, they felt that people were afraid of them and that people avoided touching them because they were treating patients with COVID-19. 110 (44%) respondents were denied social exchanges/friendships, 88 (35.2%) felt neglected by family or friends, and 71 (28.4%) lost friendships because they worked with patients with COVID-19. Stigma was experienced significantly higher in younger age (p=0.012*), resident doctors (p=0.001**) and those with longer working hours (p=0.01*). Conclusion: Doctors experience stigma from friends, family and general public due to their contact with COVID-19 patients. Experienced stigma is higher in young age and resident doctors.